Use of Benthic Macroinvertebrates as Bioindicators of Anthropogenic Impacts on Water Quality of Mae Klong River, Western Thailand - Songyot Kullasoot (Science Faculty of Chiang Mai University, 2019)
This research aimed to assess the anthropogenic impacts on benthic macroinvertebrate communities and the water quality in the Mae Klong River in Western Thailand. Samples were collected on six separate occasions from seven sampling sites between July 2011 and April 2012. All environmental variables except nitrate nitrogen were found to be significantly different depending on sampling sites (p<0.01) and seasons (p<0.05). The presence of a total of 8,901 benthic macroinvertebrates and 146 taxa was confirmed by examination of the aquatic insects and annelids that were found in the seven sampling sites. Sensitive taxa in the orders Ephemeroptera, Plecoptera and Trichoptera were more abundant at upstream collection points compared to downstream sites. Substrate disturbance from dam construction was the main cause of reduction in the diversity of benthic macroinvertebrates at the upstream sites. Additionally, organic loading caused a reduction in the abundance and taxa richness of the samples collected at the downstream sites. A significant negative correlation (p<0.01) between total suspended solids, biochemical oxygen demand and ammonium nitrogen and the benthic macroinvertebrate communities and biotic indices (BMWPThai and ASPT) indicated the anthropogenic impact existent in upstream and downstream locations of the Mae Klong River. However, the water quality of the Mae Klong River was assessed using ASPT and PBI indices that ranged in level from polluted to clean.